Evaluating the Efficacy of Project-Based Learning for Student-Athletes: A Comparative Analysis - Muhammad Faqih Al Farisi; Ferri Susanto; Anita (Journal of Interdisciplinary Sport Science Research, 2026)
This research aimed to investigate the effect of implementing the Project-Based Learning (PjBL) method on the improvement of speaking skills among eleventh-grade athletes at SMAN Keberbakatan Olahraga Kota Bengkulu. The study employed a quasi-experimental design with a quantitative approach. Data collection was conducted from August 18th to September 18th, 2025. The results indicated that while the PjBL method contributed to an improvement in athletes’ speaking skills as evidenced by the experimental class's mean score increase from 21.95 in the pre-test to 36.4 in the post-test, it was less effective than the conventional method. The control class, which utilized conventional instruction, showed a more significant improvement, with the mean pre-test score rising from 28.85 to 68.8 in the post-test. Statistical analyses confirmed a significant difference between the two groups. The findings suggest that, within this specific context, the conventional method proved more effective in enhancing speaking proficiency. This outcome is attributed to the athletes' familiarity with direct learning, which allowed for a more focused and systematic delivery of instructional material.